npj Metamaterials - Alavi, Amir H. .; Payne, Daniel; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Metamaterials focuses on the latest research and advances in the design, fabrication and applications of metamaterials and metasurfaces. The journal covers a broad range of topics including but not limited to: Advanced synthesis and fabrication techniques Mechanics and failure analysis of metamaterials Data-driven and computational design methods Integration of multifunctionality in metamaterials Bioinspired and hierarchical Metamaterials Wave manipulation, non-linearity and control using metamaterials The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by metamaterials experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Metamaterials; Nanotechnology; Nonlinear Optics; Optics; Photonics; Optical engineering; Materials; Metamaterials; Nanoscale Design, Synthesis and Processing; Nonlinear Optics; Light-Matter Interaction; Photonics and Optical Engineering; Materials Engineering